Peran Komponen Kurikulum dalam Pembeljaran Sastra Lokal di SMAN 1 Cikarang Utara - Mauludani, Seli; Pebriani, Risma; Fadhillah, Hilmy Azzah; Sukmana, Arifah Suci (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to explore how curriculum components can be the key in creating more appropriate literature learning at SMAN 1 Cikarang Utara using the Merdeka curriculum. Using a qualitative approach, this study investigates how curriculum elements such as learning objectives, lesson content, teaching methods, and evaluation are implemented in the daily context of the teaching and learning process. The results of the study indicate that the main factor in achieving adaptive learning is the ability to choose flexible learning methods and implement assessments that are tailored to the needs of each student. This study provides recommendations for schools to improve the quality of local literature learning that can be adjusted to the individual needs of each student. Keywords: curriculum components, local literature learning, merdeka curriculum